2023
DOI: 10.3390/biomedicines11061548
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Appraisal of Phase 3 Clinical Trials in Geographic Atrophy

Abstract: Geographic atrophy (GA) secondary to age-related macular degeneration is a common cause of blindness worldwide. Given the recent approval of the first therapy for GA, pegcetacoplan, we critically appraise methodological aspects of the phase 3 clinical trials published so far in this disease in relation to their design, analysis and interpretation. We reviewed some of the key attributes of all phase 3 clinical trials in GA available in the main public registry of clinical trials as of 20 May 2023. The topics di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…KITE, KESTREL and KINGFISHER, phase III studies found an intraocular inflammation in 2.2% to 4.7% of cases with brolucizumab (3 - 6 mg) versus 0.5% to 1.7% with aflibercept (2mg). These studies report a posterior involvement in the form of a retinal vasculitis in up to 1.6% [ 136 138 ]. According to the approved label, brolucizumab is contraindicated in eyes with active intraocular inflammation [ 139 ].…”
Section: Drug Related Uveitismentioning
confidence: 99%
See 1 more Smart Citation
“…KITE, KESTREL and KINGFISHER, phase III studies found an intraocular inflammation in 2.2% to 4.7% of cases with brolucizumab (3 - 6 mg) versus 0.5% to 1.7% with aflibercept (2mg). These studies report a posterior involvement in the form of a retinal vasculitis in up to 1.6% [ 136 138 ]. According to the approved label, brolucizumab is contraindicated in eyes with active intraocular inflammation [ 139 ].…”
Section: Drug Related Uveitismentioning
confidence: 99%
“…Recently, intravitreal injections of pegcetacoplan (15 mg) to slow progression of atrophy in AMD have shown an incidence of 3% intraocular inflammation, including anterior chamber cells, iritis, and anterior chamber flare, in the DERBY and OAKS phase 3 randomized controlled clinical trials [ 138 ].…”
Section: Drug Related Uveitismentioning
confidence: 99%
“…One of them-pegcetacoplan, additionally denoted as APL-2-is a PEGylated peptide inhibitor of C3 formulated by Apellis Pharmaceuticals that is administered intravitreally [6]. Moreover, on 17 February 2023, the Food and Drug Administration approved Syfovre ® (intravitreal pegcetacoplan, 15 mg, Apellis Pharmaceuticals, Waltham, MA, USA) based on a slower progression of atrophy in the DERBY and OAKS phase 3 randomized controlled clinical trials [7].…”
mentioning
confidence: 99%
“…In a tutorial, Biarnés et al [7] critically appraise the methodological aspects of phase 3 clinical trials in GA in relation to their design, analysis, and interpretation. The authors reviewed some of the key methodological attributes of phase 3 clinical trials in GA available in the main public registry of clinical trials as of 20 May 2023 (GATHER1, DERBY/OAKS, CHROMA/SPECTRI, SEATTLE, and GATE) to improve their interpretation.…”
mentioning
confidence: 99%
See 1 more Smart Citation